Course Of Making Coffee Skin Bricket to The Community in Bener Meriah Village - Rahma; Safarati, Nanda; Fatimah; M. Taufiq; Marnita (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
Whereas residents can still exploit the potential of other natural resources wasted in the village. One of them is coffee skin waste. Through this activity, the team provided training and mentoring to the people of BenerMeriah Village to be able to utilize coffee skins into coffee skin briquettes as alternative fuels. Training activities and assistance in making coffee skin briquettes to the community are carried out through certain stages. Conduct counseling about empowering coffee skin waste into coffee skin briquettes, followed by making coffee skin briquettes together. From the results of the dedication, it was obtained that thecommunity was able to utilize coffee skin waste as an alternative fuel.